2017
DOI: 10.1002/jcp.26094
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells: A new platform for targeting suicide genes in cancer

Abstract: One of the important strategies for the treatment of cancer is gene therapy which has the potential to exclusively eradicate malignant cells, without any damage to the normal tissues. Gene-directed enzyme prodrug therapy (GDEPT) is a two-step gene therapy approach, where a suicide gene is directed to tumor cells. The gene encodes an enzyme that expressed intracellularly where it is able to convert a prodrug into cytotoxic metabolites. Various delivery systems have been developed to achieve the appropriate leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 187 publications
(222 reference statements)
0
39
0
1
Order By: Relevance
“…can easily be isolated and expanded in large amounts from adult mammals without major ethical concerns; (b.) undergo targeted tropism towards growing tumors; (c.) migrate deep into the tumor microenvironment; (d.) differentiate into cells of the tumor stroma (cancer‐associated fibroblasts, pericytes and endothelial cells); (e.) have low immunogenicity and can potentially avoid immune rejection …”
Section: Introductionmentioning
confidence: 99%
“…can easily be isolated and expanded in large amounts from adult mammals without major ethical concerns; (b.) undergo targeted tropism towards growing tumors; (c.) migrate deep into the tumor microenvironment; (d.) differentiate into cells of the tumor stroma (cancer‐associated fibroblasts, pericytes and endothelial cells); (e.) have low immunogenicity and can potentially avoid immune rejection …”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have repeatedly shown that MSCs are trapped after intravenous injection [ 82 , 83 ]. Many existing methods are used to modify MSCs and the most commonly used are genetically modified MSCs [ 84 , 85 ]. The cells can transport the agents into the tumor microenvironment and greatly reduce the immune reaction in vivo through high concentration anticancer agents target tumor site.…”
Section: Effect Of Mscs On Colon Cancersmentioning
confidence: 99%
“…Viral vectors are particularly appealing because they can enable high transduction efficiency and, depending on the type of virus used, can deliver long-term stable transgene expression. The safety of cell-based therapy with the use of viral vectors is a crucial issue that has not been resolved yet, but advances in vector design have helped towards this direction ( 23 , 95 ). For example, MSCs genetically modified to express VEGF have been shown to enhance the cardioprotective effects of MSCs followed by angiogenesis effects for the treatment of acute MI, whereas Akt gene- or heme oxygenase-1 ( HO-1 ) gene-modified MSCs have been shown to dramatically improve ischemic cardiac function and MSC viability and prevent ventricular remodeling and apoptosis of cardiomyocytes and endothelial cells, thus restoring the function of infarcted hearts ( 91 , 96 98 ).…”
Section: Genetically-modified Stem Cells In Treatment Of Human Dismentioning
confidence: 99%